2019
DOI: 10.2984/73.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Kuniesaurus albiauris, a New Genus and Species of Scincid Lizard from the Île des Pins, New Caledonia, with Comments on the Diversity and Affinities of the Region's Lizard Fauna

Abstract: A new genus and species of skink, Kuniesaurus albiauris, is here described from the Île des Pins off southern New Caledonia. This new taxon possesses a unique suite of morphological apomorphies (scalation) that does not allow it to be placed in any existing Australasian eugongylid genus. It is known only from a single area in dense coastal forest on limestone, on the main island of the Île des Pins. The species area of occupancy is restricted, and the habitat occupied under threat from the spread of the highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…K . albiauris was recently discovered and described from the Ile des Pins off the southern tip of New Caledonia (Sadlier et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…K . albiauris was recently discovered and described from the Ile des Pins off the southern tip of New Caledonia (Sadlier et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The species is one of the more morphologically bizarre New Caledonian skinks with a number of unique apomorphies, and not readily aligned with any other genus in the region, and to some extent not comfortably within the Eugongylini. K. albiauris was recently discovered and described from the Ile des Pins off the southern tip of New Caledonia (Sadlier et al 2019). It is a small species with a suite of morphological apomorphies that do not allow its placement in any existing New Caledonian genus.…”
Section: Geoscincus Sadlier 1987 and Kuniesaurus Sadlier Et Al 2019mentioning
confidence: 99%
“…From these studies, two species were recognized as restricted to the Île des Pins island complex, the skink Celatiscincus euryotis and the gecko Rhacodactylus trachycephalus (Bauer et al 2012), clearly demonstrating the potential for localized island endemism. The later rediscovery of the giant skink Phoboscincus bocourti in the Île des Pins region (Ineich 2009) also likely represents the presence of another localized island endemic, as does the recent discovery of a new skink genus under description (Sadlier, Deuss et al 2019). Field studies undertaken on the Beleps in 2002 resulted in the discovery of a distinct species of crested gecko from the islands, Correlophus belepensis (Bauer et al 2012), whose sister species C. ciliatus occurs on the adjacent Grande Terre (Bauer et al 2012;Sanchez et al 2015), and of a species of Dierogekko (Bauer et al 2006a) from the region, further indicating island endemism to be a broadly ranging phenomena in the archipelago, at least on these stranded remnants of the Grande Terre, and later field studies in 2006 identified another species of Dierogekko endemic to one of the intervening islands between the Beleps and Grande Terre (Skipwith et al 2014).…”
mentioning
confidence: 99%